1988
DOI: 10.1200/jco.1988.6.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Protein A immunoadsorption in the treatment of malignant disease.

Abstract: Circulating immune complexes (CIC) are known to be present in cancer patients and are responsible for much of the cancer-associated immunosuppression. Removal or modulation of these "blocking factors" can reverse the immunosuppression. Protein A from Staphylococcus aureus has the unusual property of binding to CIC with high avidity. Use of protein A as an immunoadsorbent in extracorporeal immunotherapy affinity columns has resulted in antitumor and antiviral responses in animals. Our group developed a multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Recovery from ITP could not be accounted for by direct quantitative removal of platelet-binding IgG and CIC from patient plasma by perfusion over protein A-silica columns, as the recovery process could be initiated by removal of as little as 1 g of IgG per treatment (19,24). However, an immune modulation model based on removal of IgG-CIC from plasma is consistent with the serologic responses observed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Recovery from ITP could not be accounted for by direct quantitative removal of platelet-binding IgG and CIC from patient plasma by perfusion over protein A-silica columns, as the recovery process could be initiated by removal of as little as 1 g of IgG per treatment (19,24). However, an immune modulation model based on removal of IgG-CIC from plasma is consistent with the serologic responses observed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…However, there must be something more going on, since the administration of serum that has passed over the SPA column frequently produces fevers and chills and systemic reactions, implying that the column has added something to or activated something in the serum rather than merely taken something away. Two recent reports suggest that a small fraction of patients treated with SPA column perfusion, including those with breast cancer, may respond to the therapy [60,61].…”
Section: Biological Response Modifiersmentioning
confidence: 98%
“…In humans, partial responses have been reported in breast and colon cancers and in Kaposi's sarcoma. The largest clinical trial of SPA therapy in malignancy was reported by Messerschmidt et al (22), in which 12 weekly SPA treatments were given. Of the 87 patients 21 had partial responses, but median duration of the response or survival was not given.…”
Section: Spa Therapymentioning
confidence: 99%